A novel microcrystalline tyrosine-adsorbed, mite-allergoid subcutaneous immunotherapy: 1-year follow-up report. (October 2016) - Roger, Albert; Depreux, Nathalie; Jurgens, Yanina; Serra, Aina T; Heath, Matthew D; Garcia, Gloria; Skinner, Murray A
Aim: A 1-year follow-up study comparing the safety and tolerability of the dosing schedules, satisfaction and effectiveness of a novel microcrystalline tyrosine-adsorbed mite ( Dermatophagoides pteronyssinus )-allergoid subcutaneous immunotherapy (Acarovac Plus™) in 30 adult patients (18–65 years) with allergic rhinitis and/or asthma.Materials & methods: The effectiveness of the product was assessed by nasal provocation test measuring peak nasal inspiratory flow/symptoms, in vitro immunologic changes (IgE, IgG4 and IL-10) and Treatment Satisfaction Questionnaire for Medication.Results: No adverse events were reported during dosing schedules. Significant decreases in symptom scores and drop of peak nasal inspiratory flow in follow-up visits (4 weeks and 1 year) were recorded. Significant increases in IgG4-specific antibody titers and IL-10 were exhibited.Conclusion: Significant decreases in clinical symptoms and immunological parameters were observed, accompanying a high level of patient satisfaction and tolerance.